Sztuka potrydencka na Śląsku na przykładzie kościoła św. św. Stanisława i Wacława w Świdnicy. Założenia teoretyczne i praktyka artystyczna - Głowacki, Małgorzata (Acta Universitatis Lodziensis. Folia Historica, 2008)
„After Trident Council art” term refers to the sacral artistic realizations which originated after the Trident Council (1545-1563). Generally, the foundations of this art were formulated during the last (XXVth) session of the Council (3-4 December 1563) in the decree entitled De invocatione, veneratione el reliqvis sanctorum, et sacris imaginibus. Because the decree did not give answer to many very important questions for artists, which were born during the artistic practice, detailed solutions were found by the Catholic art theoreticians, such as Johannes Molanus, Andrea Possevino, Gabriele Paleotti or Carlo Borromeo. The Church of St. Stanislas and Vaclav in Świdnica proves that decisions of the Trident Council with reference to the sacral art were strictly realized. The formal and ideological analysis of this structure confirms that within the space of the parochial church in Świdnica were realized all topics recommended by the Council: The Christology, The St. Mary’s Cult and The Hagiography. In representations of Jesus Christ was marked the role of The Eucharist in redeem, in the scenes in which St. Mary was presented, according to the instructions of the Catholic Church, were heightened the elements such as her Immaculate Conception and Advocacy which distinguished St. Mary from other women. Finally, in the representations of the Saints, the personages of the church patrons and the founders of the Society of Jesus were marked. Other motifs visible in the church decoration (The Trinity, The Salomon Temple, The Triumph of the Church) were repercussions of the local religious and political situation in Silesia in 17th and 18th century.